Evaluation of the OptiMAL® test for diagnosis of malaria in Venezuela - Zerpa, Noraida; Pabón, Rosalba; Wide, Albina; Gavidia, Magda; Medina, Mehudi; Cáceres, José Luis; Capaldo, Jacinta; Baker, Meghan; Noya, Oscar (Investigación Clínica, 2013)
We evaluated the OptiMAL® rapid dipstick test by comparing it with the conventional standard thick-blood film method, for the detection of malaria in two groups of individuals from different Venezuelan endemic areas.One of the groups consisted of individuals with malaria-like symptoms (n =113) and the other of asymptomatic individuals (n = 89). The classical microscopy analysis of these populations determined that 67.5% were infected with P. vivax, 31.3% with P. falciparum, and 1.2% with mixed infections. The OptiMAL® test showed 96.4% sensitivity, 100% specificity, 100% positive predictive value, 97.5% negative predictive value and optimal concordance (kappa = 0.97), capable of de tecting any malaria infection in the evaluated population. However, these parameters were lower when the parasitaemia was Â£ 300 par a sites/Î¼L. Freezing of the samples did not affect the sensitivity and specificity of the test. We conluded that this rapid malaria test is sensitive and specificfor rapid diagnosis of malaria in the field and it is a complement to conventional microscopy.